Assessment of the Pharmacokinetics and Safety of Spesolimab, a Humanised Anti-interleukin-36 Receptor Monoclonal Antibody, in Healthy Non-Japanese and Japanese Subjects: Results from Phase I Clinical Studies - Joseph, David; Thoma, Christian; Haeufel, Thomas; Li, Xiujiang (Clinical pharmacokinetics, 2022)
Background and Objective The interleukin-36 signalling pathway is associated with pathogenesis of a number of inflammatory diseases. Spesolimab is a selective, humanised, IgG1 antibody that targets the interleukin-36 receptor. We aimed to evaluate the pharmacokinetics, safety and tolerability of single and multiple doses of spesolimab in healthy non-Japanese and Japanese subjects. Methods Five phase I clinical studies (three placebo-controlled dose-escalation, two open-label) were conducted in healthy volunteers; single or multiple doses of spesolimab were administered by intravenous infusion or subcutaneous injection. Plasma samples were collected to investigate the pharmacokinetics of spesolimab and evaluate changes with respect to dose, frequency of dosing, formulation and injection site. Immunogenicity, safety and tolerability were also assessed. Results Intravenous spesolimab exhibited target-mediated drug disposition at low doses (0.01–0.3 mg/kg) and linear kinetics at doses ≥ 0.3 mg/kg. Steady state was not attained after the fourth weekly dose because of the long half-life (3–5 weeks). Bioavailability of subcutaneous spesolimab increased with increasing dose over the range of 150–600 mg and was higher when administered to the thigh than to the abdomen. The pharmacokinetic profile was consistent between Japanese and non-Japanese subjects. Positive anti-drug antibody responses occurred during the terminal phase of the spesolimab concentration–time profile in 26.7–33.3% and 16.7–37.5% of subjects receiving intravenous and subcutaneous spesolimab, respectively. The impact of anti-drug antibodies on spesolimab pharmacokinetics was low in healthy volunteers, with the impact on spesolimab plasma concentrations only observed in a few subjects at higher titres (≥ 11,400). No serious adverse events were reported; intravenous doses up to 1200 mg were well tolerated in healthy volunteers. Conclusions The pharmacokinetic profile and safety data obtained from these phase I clinical studies have been used to guide spesolimab dosing in clinical studies of patients with interleukin-36-mediated diseases. Clinical Trial Registration For Studies 1–5, NCT02525679, NCT02852824, NCT03100903, NCT03123094, NCT03617835.